2015
DOI: 10.1108/oth-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

“Why am I to blame when the law is on my side?” A study of crises, public opinion and frames

Abstract: 2015),"The Montalbano effect: re-branding Sicily as a tourist destination?", On the Horizon, Vol. 23 Iss 4 pp. 342-351 http:// dx.Access to this document was granted through an Emerald subscription provided by emerald-srm:305060 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This strategic use of frames in communication has been researched in discourse studies (Tannen 1993, Ensink andSauer 2003), and is further developed in this volume with new research evidence. Holmgreen (Holmgreen 2015 and in this volume), for instance, studies the resilience of public frames to news media frames during public disputes, which demonstrates the conceptual grounding of the framing effect.…”
Section: Exploring Conceptual Metaphors and Frames With A Discourse And Cognitive-based Approachmentioning
confidence: 79%
“…This strategic use of frames in communication has been researched in discourse studies (Tannen 1993, Ensink andSauer 2003), and is further developed in this volume with new research evidence. Holmgreen (Holmgreen 2015 and in this volume), for instance, studies the resilience of public frames to news media frames during public disputes, which demonstrates the conceptual grounding of the framing effect.…”
Section: Exploring Conceptual Metaphors and Frames With A Discourse And Cognitive-based Approachmentioning
confidence: 79%
“…However, as has been demonstrated in later empirical research, identifying something as a crisis is sometimes difficult and may happen too late, leading to 7 unsuitable and even damaging response strategies. This suggests that crisis typologies can only function as general guidelines to the identification and handling of crises (Holmgreen, 2015). Part of the reason for this may be found in the fact that contextual factors play a decisive role in determining when and how something becomes a crisis according to stakeholders, just as the channels through which crisis communication takes place influence the attributions stakeholders assign to the organisation (cf.…”
Section: Crisis Responsibility and The Relevance Of Conversational Hu...mentioning
confidence: 99%
“…The positive nature of corporate image was mentioned in studies in relation to the rapidity of information sharing (Holmgreen, 2015;Joachim et al, 2018), as well as the ability of social media to help organizations to maintain and protect a strong reputation (Oliveira & Figueira, 2015). Thus, for example, the research conducted on the whole population of Higher Polytechnic Portuguese Education Institutions revealed that it is important to invest heavily in communicating corporate identity via social media in order to create and maintain a positive corporate image, both internally and externally (Oliveira & Figueira, 2015).…”
Section: Corporate Identity and Social Mediamentioning
confidence: 99%